Update on Cardiovascular Risk and Obesity in Psoriatic Arthritis - Ramírez, Julio; Azuaga-Piñango, Ana Belén; Celis, Raquel; Cañete, Juan D. (Frontiers in Medicine, 2021)
PsA is characterized by a high prevalence of cardiovascular (CV) comorbidities. Recognizing these comorbidities is critical due to their influence on the quality of life and the choice of therapy. Imaging techniques also play an important role in the evaluation of the CV risk in psoriatic disease, improving the prediction of CV events when combined with clinical scores as a predictive tool. Meta-analyses point to a significant reduction in the incidence of CV events associated with the suppression of inflammatory activity when using systemic therapies. Consequently, the mortality rate in PsA patients has fallen in the last 40 years and is now similar to that of the general population, including cardiovascular causes. Obesity is an especially relevant CV comorbidity in patients with psoriatic disease, most of whom are overweight/obese. Body mass index (BMI) is a risk factor for PsA and a causal relationship with psoriasis has been demonstrated by Mendelian randomized studies. The study of fat distribution shows that patients with psoriasis are characterized by visceral fat accumulation, which correlates with CV risk measurements. These findings suggest that approaches to the prevention and treatment of psoriatic disease might come from targeting adiposity levels, in addition to the immune pathways. Weight loss treatment with low energy diets in patients with PsA has been associated with significant improvements in disease activity. Novel strategies using a multimorbidity approach, focused more on patients outcomes, are necessary to better address comorbidities, improve clinical outcomes and the quality of life of patients with psoriatic disease.